Rural women of the cone sul of rondonia: black, old-aged and forgotten - Coelho, Lilian Reichert; Ruas, Larissa Cristina Pereira (Revista Hipótese, 2016)
In a hybrid of journalistic report and profile, we present our contact with two rural women remaining of a rural camp in Rondonia’s countryside. This journalistic production had its origins in the scientific research Project Gender, media and public policies in Rondonia: Critical Discourse Analysis of the governmental program Citizenship Territories and proposals of communication and citizenship to/with rural worker women mobilized developed within HIBISCUS – Group of Research and Extension in Communication, Discourse and Gender, IN University of Rondonia, between the years of 2012 and 2014, with funds of CNPq and SPM.